Swirling Flow Field inside a Hollow Turbine Shaft for an Internal Cooling Air System - Tadaharu Kishibe; Shojiro Kaji (International Journal of Rotating Machinery)
The swirling flow field in an internal cooling air system in which the fluid passes through an inducer, a hollow turbine shaft, and a cavity between two disks (referred to as a wheel space) is solved using computational fluid dynamics and the pressure fluctuations on the hollow shaft wall surface are measured.